Réponses

Meilleure réponse !
2014-05-20T19:10:14+02:00
Résous le équations suivantes :

a) 4(x+5) = 10x + 3
4x + 20 = 10x + 3
4x - 10x = 3 - 20
- 6x = -17
x = 17/6

b) 3(x-2) = 6(x+4)
3x - 6 = 6x + 24
3x - 6x = 24 + 6
- 3x = 30
x = - 30/3
x = - 10

c) 7x - (5x + 3) = 5(x - 3) + 2
7x - 5x - 3 = 5x - 15 + 2
7x - 5x - 5x = - 15 + 2 + 3
- 3x = - 10
x = 10/3

d) 7(n + 2) - 3 = 25 - (3n + 4)
7n + 14 - 3 = 25 - 3n - 4
7n + 3n = 25 - 4 - 14 + 3
10n = 10
n = 10/10
n = 1

e) 4y + 3(4y - 2) = 3(y+1)

4y + 12y - 6 = 3y + 3
4y + 12y - 3y = 3 + 6
13y = 9
y = 9/13